The Axiological Dimension of Islamic Education - Nasrullah Nasrullah; Jaftiyatur Rohaniyah; Abdullah Hanani (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
Axiology is a theory about a value, benefit or everything that is known. Axiology divided into two parts, namely ethic and aesthetic. The ethics are divided into two parts, the first is descriptive ethics and the second is normative ethics, as well as Aesthetics, there are two parts of Aesthetics, the first is Descriptive Aesthetics and the second is Normative Aesthetics. While the source of value has two parts, namely, divine values and Inaniyah values. Characteristics and value levels are also divided into two, namely objective or subjective values and absolute or changing values. In the essence of value, there are important points such as: the value of life, the value of enjoyment, the value of usability, the value of intellectuals, the value of ethics, the value of aesthetics, and the value of religion. Islamic education has a goal, namely to make students as human beings who develop towards a better and become ethical human beings and have a personality that is in accordance with Islamic teachings, both in terms of spiritual, scientific, scientific, both individually and collectively. Values are closely related to Islamic education because Islamic education is a process of achieving perfection in terms of the ability of students in accordance with Islamic teachings.